The machine that therefore I am. Alternatives to thinking technologies and subjects - Revello, Roberto (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
With regard to the question of the new ethical, social and political subjectivity emerging in the current era of technological revolutions, this paper proposes two points of inescapable reflection: 1. Technologies are not simple “objects” as a certain kind of philosophy wants. Overcoming the “cultural dissociation” of which we speak, for example, Gilbert Simondon can be useful to rid us of a metaphysical determinism that would removes all sense of responsibility about which technologies are and should be developed. 2. The loss of political effectiveness by the intellectual critique and the progressive political movements cannot be solved by recovery of the modern “subjectivity”. If this concept can be identified in a fatal binary logic of inclusion / exclusion, subjectivation / subjection, if the personalistim is under attack by challenges that exceed the limits of classical definition (individual, nation state), if in short the modern subjectivity is unusable, the current disorientation will not be resolved by removing this restless opacity and this impotence. This means that we should accept the challenge, even at the cost of seeing very little. Keywords: Technologies, Humanities, Subjectivity, Plasticity, Digital Culture.